The Structural Performance Analysis of The BPJN Bengkulu Office Building Using The Response Spectrum Method Based on SNI 1726:2019 - Felny, Fideriko (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
The Office Building of the Bengkulu National Road Implementation Agency (BPJN) is designed to function as a central facility for the planning, procurement, construction, and maintenance of road and bridge infrastructure. This two-story building is planned to reach a total height of 11.563 meters. Unlike conventional buildings, it features a distinctive architectural design with an oval floor plan, resulting in an unconventional structural configuration. The structural works encompass the design of key components including floor slabs, beams, columns, shear walls, and the foundation system. For the superstructure, a Special Moment Resisting Frame System (SMRFS) was selected, as it is suitable for regions with high seismic risk (seismic design categories D, E, and F). This study aims to assess the structural performance of the building using the response spectrum analysis method in accordance with SNI 1726:2019. The research methodology was carried out in several stages, including data collection from both field observations and supporting documents, structural modeling, load analysis, structural analysis, and evaluation of structural performance. The structural model was developed based on official design drawings. The loads considered in the analysis include both gravity and lateral loads. The results showed that mass participation exceeded 90%, and both the structural period and base shear values complied with the criteria set by SNI 1726:2019. The inter-story drift results were within the allowable limits, indicating that the building is structurally stable. Based on the calculated drift ratio, the building's performance level falls under the Immediate Occupancy (IO) category.